Combining NHC–Cu and Brønsted Base Catalysis: Enantioselective Allylic Substitution/Conjugate Additions with Alkynylaluminum Reagents and Stereospecific Isomerization of the Products to Trisubstituted Allenes1. Issue 30 (18th June 2013) - Dabrowski, Jennifer A.; Haeffner, Fredrik; Hoveyda, Amir H.
<x xml:space="preserve">Abstract</x> All‐catalytic route to trisubstituted allenes: The first examples of catalytic enantioselective allylic substitution reactions that involve alkyne‐based nucleophiles and lead to products having tertiary stereogenic centers are followed by an exceptionally stereospecific amine‐catalyzed isomerization to trisubstituted allenes (see picture; NHC=N‐heterocyclic carbene).<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>